MRI-Based Radiomic Signature Identifying Secondary Loss of Response to Infliximab in Crohn's Disease - Feng, Jing; Feng, Qi; Chen, Yueying; Yang, Tian; Cheng, Saiming; Qiao, Yuqi; Shen, Jun (Frontiers in Nutrition, 2022)
Up to 50% of patients with Crohn's disease (CD) experience secondary loss of response (SLR) to infliximab. Patients with SLR may show clinical signs of iron deficiency as a result of inflammation despite being iron-replete. The magnetic resonance imaging (MRI)-based radiomic index, R2*, can detect changes in iron metabolism. Therefore, the R2* parameter has considerable potential for detection of SLR to infliximab. The aims of this study were to explore the correlation between R2* and inflammation and to develop a non-invasive nomogram based on R2* to identify SLR to infliximab in patients with CD. Three hundred and twenty-two infliximab-treated patients with CD who underwent magnetic resonance enterography within 2 weeks before or after 54 weeks of infliximab therapy were divided into training and validation datasets at a ratio of 8:2. Point-biserial analysis was conducted to confirm the relationship between R2* and inflammation. A multivariate logistic regression model was created using R2*, CRP and hemoglobin (OR, 1.10, 1.04 and 0.98; P < 0.05). Receiver-operating characteristic curves and the Hosmer-Lemeshow test were used to assess the performance of the model. A correlation between R2* and inflammation was identified. Different trends in R2* and iron status indices were observed between patients with responsive and non-responsive CD, which is worthy of further study. The model was converted to a visualized nomogram that had a good ability to discriminate the outcomes of infliximab therapy with an area under the curve of 0.723 (95% CI, 0.661–0.785) in the training dataset and 0.715 (95% CI, 0.587–0.843) in the validation dataset. We confirmed a correlation between R2* and inflammation in patients with CD. Based on the MRI-based radiomic signature, a novel nomogram was established and validated to facilitate individualized identification of SLR to infliximab in patients with CD.